a(p+q)+2b(p+q)+a(p-q)+2b(p-q)=

Simple and best practice solution for a(p+q)+2b(p+q)+a(p-q)+2b(p-q)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a(p+q)+2b(p+q)+a(p-q)+2b(p-q)= equation:


Simplifying
a(p + q) + 2b(p + q) + a(p + -1q) + 2b(p + -1q) = 0
(p * a + q * a) + 2b(p + q) + a(p + -1q) + 2b(p + -1q) = 0
(ap + aq) + 2b(p + q) + a(p + -1q) + 2b(p + -1q) = 0
ap + aq + (p * 2b + q * 2b) + a(p + -1q) + 2b(p + -1q) = 0
ap + aq + (2bp + 2bq) + a(p + -1q) + 2b(p + -1q) = 0
ap + aq + 2bp + 2bq + (p * a + -1q * a) + 2b(p + -1q) = 0
ap + aq + 2bp + 2bq + (ap + -1aq) + 2b(p + -1q) = 0
ap + aq + 2bp + 2bq + ap + -1aq + (p * 2b + -1q * 2b) = 0
ap + aq + 2bp + 2bq + ap + -1aq + (2bp + -2bq) = 0

Reorder the terms:
ap + ap + aq + -1aq + 2bp + 2bp + 2bq + -2bq = 0

Combine like terms: ap + ap = 2ap
2ap + aq + -1aq + 2bp + 2bp + 2bq + -2bq = 0

Combine like terms: aq + -1aq = 0
2ap + 0 + 2bp + 2bp + 2bq + -2bq = 0
2ap + 2bp + 2bp + 2bq + -2bq = 0

Combine like terms: 2bp + 2bp = 4bp
2ap + 4bp + 2bq + -2bq = 0

Combine like terms: 2bq + -2bq = 0
2ap + 4bp + 0 = 0
2ap + 4bp = 0

Solving
2ap + 4bp = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4bp' to each side of the equation.
2ap + 4bp + -4bp = 0 + -4bp

Combine like terms: 4bp + -4bp = 0
2ap + 0 = 0 + -4bp
2ap = 0 + -4bp
Remove the zero:
2ap = -4bp

Divide each side by '2p'.
a = -2b

Simplifying
a = -2b

See similar equations:

| -3(3p+3)-2(4-8p)-3(9+2p)=0 | | -6.8+2.6+x=9.2 | | 2x^2-53x+141=0 | | 5(x+4)-16=2(x+3)-2 | | -8(3b+2)+(25b-5)=0 | | 20y^2+4y-7=0 | | 22+5=-3x+15 | | 13r+1=7r+8 | | -8x+9x-21=(-12)-16 | | 2t-6=3t+14 | | -386=14+10x | | -10+y=14 | | 12x-6=5x+15 | | .25+.03x=.37 | | 16+x-(11)=18-(5) | | (x-6)-(x+8)=8x | | 12f=-60 | | 6v^2+90=-48v | | 7.4-y=8.3 | | 12x=-2+8x | | x^3-3x=17.2 | | -28=-2c | | -40x^6-5x^5= | | .3x-.7=.5 | | 0.06*200= | | -7+b=-11 | | -48=12a | | 18d^2-89d=-84 | | 7x+4=11x-12 | | y^2-4x^2=20 | | 3(1.7x+12)=46.2 | | ax+2bx+ay+2by= |

Equations solver categories